Implementation of physics education in Nature; A pioneer rescue team study: an explanation by physics - (:unkn) unknown (AMER INST PHYSICS, 2007)
Within this research, it is generally aimed at constituting a sample implementation which shapes the contents of physics course together with its social facet and at forming a platform and starting debates for the contents. Within that purpose, we have conglomerated the students, their professor and the volunteers from the public body responsible for civil services such as the protection and maintenance of factories, power plants, rescue of civilians, and etc. to call on duty in instances of war or extra-ordinary circumstances, named civilian defence. Two camping activities in which various performances were fulfilled were held together with the students. The study focuses on sampling one of the performances which is the crossing a steam and a pond by a rope tied to trees in each ends. The focused study neither orients for nor goals any inspiration for civilian defence purposes. Civilian defence purposes are side-products and they have not been covered in the study. The main aims of this study are monitoring the instances of critical awareness in the students and presenting the samples of the process as a case study.
Keywords: outdoor physics; context-dependent problems; civilian volunteers